Data Privacy and Business Performance of E-commerce Industry: Towards Cybersecurity through Transparency and Control - Priya Sukrirthanandan; Salman Sarwar; Sana Ashraf (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: A crucial element of the modern digital ecosystem is data privacy. A comparable viewpoint is seen in the realm of e-commerce, which has emerged as the primary economic engine on a global scale. The growth in the consumer base and the sheer quantity of data being transferred within the e-commerce platforms constitute a serious risk. In compliance with international regulations, e-commerce platforms are implementing data privacy rules that include transparent and control-centric processes. Theoretical framework: The current study explored how Malaysian e-commerce enterprises' commercial performance is fueled by data privacy rules' control and transparency components. A two-pronged approach was taken in conducting the research using qualitative and quantitative methodology. Literature review: First, the transparency and control features of the data privacy policies of a chosen group of e-commerce enterprises were qualitatively benchmarked. The findings indicated that while Carousell, Ezbuy, and Mudah are some of the e-commerce companies with low levels of transparency and control practices, Methods: Lazada and Shopee have the highest levels of transparency and control practices within their data privacy policies. Subsequently, the analysis was further triangulated with a quantitative analysis from 379 respondents. The data processing and results indicate the increased transparency & control of data privacy policy practices for business performance of e-commerce companies. It includes the internal, performance, and practice benchmarking for e-commerce platforms operating in Malaysia. Results: There is specific stress on the transparency and control sections of data privacy for each of the e-commerce platforms operating in Malaysia. Implications: This research recommends the transparent and controlled review of the data privacy policies on the e-commerce platforms for effective communication, privacy, and behavioral business decisions. Novelty: the study will help setting corporate digital business to ensure cybersecurity and trust of the customer in Malaysia. The serious concern of customer digital information is aptly and rightly channeled to make further customer satisfied. The study output will help policy makers to enhance business with the trust of the customer for the obtained information.